A systematic review and meta-analysis of the ability of analgesic drugs to reduce metastasis in experimental cancer models. Issue 10 (October 2015) - Hooijmans, Carlijn R.; Geessink, Florentine J.; Ritskes-Hoitinga, Merel; Scheffer, Gert-Jan
Abstract : Abstract: Analgesics are commonly used to manage pain in cancer patients. It has been suggested that there might be a relation between analgesics and the outgrowth of metastases. Opioids might increase and non-steroidal anti-inflammatory drugs decrease the risk of metastasis. Robust analysis of all preclinical evidence, however, has so far been lacking. Therefore, we conducted a systematic review and meta-analysis on the effect of treatment with analgesics on metastasis in experimental animal models. One hundred forty-seven studies met the inclusion criteria. Study characteristics, outcome data on the number, and incidence of metastases were extracted, and methodological quality was assessed. In the meta-analysis, we included 215 (±4000 animals) and 137 (±3000 animals) comparisons between analgesic vs control treatment, respectively, on the number and incidence of metastases. Overall, treatment with analgesics significantly decreases the number and risk of metastasis. This effect appears mainly to be the consequence of the efficacy of NSAIDs. Other factors that modify the efficacy are species, type of NSAIDs administered, timing, and duration of treatment. There is no evidence indicating that treatment with any analgesics increases the occurrence of metastases. Our findings appear robust for the various animal models and designs included in this review, which increases our confidence in the result and translatability to the clinical situation. Abstract : Supplemental Digital Content is Available in the Text.